ChemInform Abstract: Compositional and Structural Versatility in an Unusual Family of anti‐Perovskite Fluorides: [Cu(H2O)4]3 [(MF6)(M′F6)]. Issue 39 (September 2016) - Felder, Justin B.; Yeon, Jeongho; Smith, Mark D.; zur Loye, Hans‐Conrad
Abstract: Crystals of the anti‐Perovskites (III), (V), (VIII), (IX), and (X) are hydrothermally prepared with yields greater than 90% and characterized by single crystal XRD, UV/VIS spectroscopy, and magnetic measurements.